Effect of herbal methionine on productive performance of broiler chicken - Oñate Mancero, Francisco Javier (2016)
We evaluated the performance of herbal methionine as a potential substitute for synthetic methionine in fattening chickens. To measure the effectiveness of amino acids from the two aforementioned sources, we assessed three treatments: T0 (dl- methionine), T1 (50% dl-methionine + 50% herbal methionine) and T2 (T2 herbal methionine). We used 192 Cobb-500 chickens, distributed in three treatments and four replications. Data were analyzed by means of a completely randomized design using Tukey’s Test and an overall risk level of0.05. The study had four variables: food consumption, body weight, feed conversion and the European efficiency index. Using InfoStat 2013, results showed that T0 had the highest weight value 2556.10 g (±50.70), with no significant difference between groups. According to the previous parameter, the highest food consumption value was T0 with 1257.43 g (±31.85), with no significant difference between groups. With respect to feed conversion, T2 had the highest numerical efficiency (1.63; ±0.03) when compared with T0 1.64 (±0.03) and T1 1.65 (±0.03), but statistical similarity (p>0.05). The European efficiency index yielded a higher value (371.04) when compared with the other treatments because there was no mortality in chickens treated with synthetic methionine T1 (365.07) and T2 (342.72). We concluded that herbal methionine can be used as a substitute for dl-methionine in partial or total form.